Diatomite-immobilized BiOI hybrid photocatalyst: Facile deposition synthesis and enhanced photocatalytic activity - Li, Baoying; Huang, Hongwei; Guo, Yuxi; Zhang, Yihe (Applied surface science, 2015)
•A novel diatomite-immobilized BiOI hybrid photocatalyst has been prepared by a facile one-step deposition process for the first time.•The diatomite-immobilized BiOI hybrid photocatalyst exhibits much better photocatalytic performance.•This enhancement should be attributed to that diatomite can play as an excellent carrier platform to increase the reactive sites and promote the separation of photogenerated electron–hole pairs.•This work shed new light on facile fabrication of novel composite photocatalyst based on natural mineral. A novel diatomite-immobilized BiOI hybrid photocatalyst has been prepared by a facile one-step deposition process for the first time. The structure, morphology and optical property of the products were characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and UV–vis diffuse reflectance spectroscopy (DRS). The photocatalytic performance of the as-prepared BiOI/diatomite photocatalysts was studied by photodegradation of Rhodamine B (RhB) and methylene blue (MB) and monitoring photocurrent generation under visible light (λ>420nm). The results revealed that BiOI/diatomite composites exhibit enhanced photocatalytic activity compared to the pristine BiOI sample. This enhancement should be attributed to that diatomite can play as an excellent carrier platform to increase the reactive sites and promote the separation of photogenerated electron–hole pairs. In addition, the corresponding photocatalytic mechanism was proposed based on the active species trapping experiments. This work shed new light on facile fabrication of novel composite photocatalyst based on natural mineral.